Dynamic spectral cues do not affect human sound localization during small head movements - McLachlan, Glen; Majdak, Piotr; Reijniers, Jonas; Mihocic, Michael; Peremans, Herbert (Frontiers in Neuroscience, 2023)
Natural listening involves the constant deployment of small head movement. Spatial listening is facilitated by head movements, especially when resolving front-back confusions, an otherwise common issue during sound localisation under head-still conditions. The present study investigated which acoustic cues are utilised by human listeners to localise sounds using small head movements (below $±10^°$ around the center). The stimulus conditions included the interaural time difference (ITD), interaural level difference (ILD), monaural spectral shape (MSS) and their dynamic counterparts: dynamic ITD (dITD), dynamic ILD (dILD) and dynamic MSS (dMSS). They were presented under three movement conditions: no movement, head rotations over the yaw axis and over the pitch axis. The results show that even small yaw rotations provide a remarkable decrease in front-back confusion rate, whereas pitch rotations did not show much of an effect. Furthermore, MSS cues improved localisation performance even in the presence of dITD cues. However, performance was similar between stimuli with and without dMSS cues. This indicates that human listeners require the correct MSS cues at the onset of a stimulus, but do not rely on dMSS cues to localise sounds even when utilising head movements.